Assessing the sustainability impacts of innovative forest management and operation practices in Norway - Wallius, Venla (2020)
In order to combat climate change and related global challenges, transition from fossil-based economy towards more sustainable bioeconomy that relies on renewable materials and resources is crucial. Wood is a versatile material that can significantly contribute to bioeconomy transition and is of great importance for example in most Nordic countries. In order to improve the wood biomass availability, new and innovative forest management practices and operations need to be adopted. The impacts of such innovative practices and operations, however, need to be assessed. This Master’s thesis explores future scenarios to improve forest management practices and operations using Norway as a case example. Main emphasis is given to the impact assessment of these innovative practices. The scenarios included in this study are corridor thinning, nitrogen and nutrient mix fertilization, and the adjustment of harvester head settings. The impacts of these selected scenarios are assessed using a set of indicators chosen to represent the various aspects of sustainability. Indicators used include employment (social sustainability), production costs (economic sustainability), and greenhouse gas emissions based on energy usage (ecological sustainability). The results of the thesis show that when taking into account the increase in biomass availability as well as environmental, economic and social impacts per cubic metre of harvested wood biomass, the fertilization of spruce-dominated forests seems to have the biggest potential in Norway. Fertilization is decreasing both production costs and fuel consumption, relative per cubic metre of harvested wood biomass, while increasing forest yield. Corridor thinning can promote efficiency in first thinnings in pine-dominated forests, decreasing relative production costs and fuel consumption as well as subsequent greenhouse gas emissions while having no effect in forest productivity. It could also be possible to utilize suitable scenarios together in order to enhance wood biomass availability while reducing relative emissions and costs.